WOMEN AND CHILDREN 'EMPOWERMENT IN ANABANUA VILLAGE THROUGH ENGLISH LEARNING USING A COLLABORATIVE LEARNING APPROACH - Amiruddin Amiruddin; Musdalifah Musdalifah (Perkumpulan Dosen Muslim Indonesia, 2021)
Academicians or lecturers are responsible for a variety of topics in villages in order to tackle society's difficulties. Anabanua is a village with the distinction of being a developed village in terms of both natural and human resources. Even though society has a poor income, the spirit of society is strong. As a result, a community service team in Anabanua, Kabupaten Wajo, has begun to assist children and teenagers in learning English. Collaborative learning is one of the approaches utilized in this community service activity because it engages and gives learners plenty of opportunities to share and discuss information and solve problems. As a result of using the collaborative learning strategy, learners are expected to be more engaged in learning and cooperating, allowing them to apply their learning and collaboration habits in the workplace. The outcomes of the community service reveal that assistance and empowerment in learning English have a beneficial impact on learners and a positive response from the community. Learners' empowerment has a critical role in boosting their motivation and raising their achievement levels. The community service activity is anticipated to be sustainable and to develop into a partnership between institutions and villages, allowing the institutions to contribute to the shaping of a smart, wise, and prosperous society.